Fifteen-year outcomes after monitoring, surgery, or radiotherapy for prostate cancer - Hamdy, FC; Donovan, JL; Lane, JA; Metcalfe, C; Davis, M; Turner, EL; Martin, RM; Young, GJ; Walsh, EI; Bryant, RJ; Bollina, P; Doble, A; et al. (Massachusetts Medical Society, 2023)
BACKGROUND: Between 1999 and 2009 in the United Kingdom, 82,429 men between 50 and 69 years of age received a prostate-specific antigen (PSA) test. Localized prostate cancer was diagnosed in 2664 men. Of these men, 1643 were enrolled in a trial to evaluate the effectiveness of treatments, with 545 randomly assigned to receive active monitoring, 553 to undergo prostatectomy, and 545 to undergo radiotherapy.